1998
DOI: 10.1002/srin.199801599
|View full text |Cite
|
Sign up to set email alerts
|

Mixing enthalpy measurements in the liquid ternary system iron‐nickel‐chromium and its binaries

Abstract: The mixing enthalpies of liquid binary iron‐nickel, nickel‐chromium and iron‐chromium alloys were measured by levitation alloying calorimetry. The mixing enthalpy of iron‐nickel alloys is asymmetric and was described by an equation according to the modified quasichemical solution model. Liquid nickel‐chromium alloys were determined to conform to a regular solution model whereas the system iron‐chromium behaves ideally. Based upon the analytical descriptions obtained for the binary systems an isoenthalpy diagra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…A minimum of about ÿ5 kJ/mol at x Ni ¼ 0.6 is indicated. Thiedemann et al [44] could also describe their results using an equation according to the modified quasichemical solution model.…”
Section: Feenimentioning
confidence: 99%
See 1 more Smart Citation
“…A minimum of about ÿ5 kJ/mol at x Ni ¼ 0.6 is indicated. Thiedemann et al [44] could also describe their results using an equation according to the modified quasichemical solution model.…”
Section: Feenimentioning
confidence: 99%
“…More recently the enthalpy of mixing at concentrations up to 46 at.% Ni at 1900 K and up to 25 at.% Fe at 1913 K was measured by Thiedemann et al [44] using levitation drop calorimetry. The results agree reasonably well with previous data [43,42,40] as shown in Fig.…”
Section: Feenimentioning
confidence: 99%
“…Knudsen cell þ mass spectrometry Waseda et al [102] Activity of Fe and Ni 1560 X-ray diffraction Tomiska [103] Activity of Fe and Ni 1600 Knudsen cell þ mass spectrometry Thiedemann et al [104] Enthalpy of mixing 1627, 1640 Levitation direct calorimetry b e List of thermodynamic measurements on the g-(FeeNi) phase considered in this work…”
Section: Referencementioning
confidence: 99%
“…In addition, it should be noted that the mixing enthalpies of the bcc and liquid phase have been measured by several authors. The most recent are those of Batalin et al [45], Iguchi et al [46] and Thiedemann et al [47]. Zaitsev et al [48] have reported the measurements of activities at different temperatures.…”
Section: Thermodynamic Datamentioning
confidence: 99%